Cancer treatment and survivorship statistics, 2022. (23rd June 2022) - Miller, Kimberly D.; Nogueira, Leticia; Devasia, Theresa; Mariotto, Angela B.; Yabroff, K. Robin; Jemal, Ahmedin; Kramer, Joan; Siegel, Rebecca L.
Abstract: The number of cancer survivors continues to increase in the United States due to the growth and aging of the population as well as advances in early detection and treatment. To assist the public health community in better serving these individuals, the American Cancer Society and the National Cancer Institute collaborate triennially to estimate cancer prevalence in the United States using incidence and survival data from the Surveillance, Epidemiology, and End Results cancer registries, vital statistics from the Centers for Disease Control and Prevention's National Center for Health Statistics, and population projections from the US Census Bureau. Current treatment patterns based on information in the National Cancer Database are presented for the most prevalent cancer types by race, and cancer‐related and treatment‐related side‐effects are also briefly described. More than 18 million Americans (8.3 million males and 9.7 million females) with a history of cancer were alive on January 1, 2022. The 3 most prevalent cancers are prostate (3, 523, 230), melanoma of the skin (760, 640), and colon and rectum (726, 450) among males and breast (4, 055, 770), uterine corpus (891, 560), and thyroid (823, 800) among females. More than one‐half (53%) of survivors were diagnosed within the past 10 years, and two‐thirds (67%) were aged 65 years or older. One of the largest racial disparities in treatment is for rectal cancer, for which 41% of Black patients with stage I disease receive proctectomy or proctocolectomy compared to 66% of White patients. Surgical receipt is also substantially lower among Black patients with non‐small cell lung cancer, 49% for stages I‐II and 16% for stage III versus 55% and 22% for White patients, respectively. These treatment disparities are exacerbated by the fact that Black patients continue to be less likely to be diagnosed with stage I disease than White patients for most cancers, with some of the largest disparities for female breast (53% vs 68%) and endometrial (59% vs 73%). Although there are a growing number of tools that can assist patients, caregivers, and clinicians in navigating the various phases of cancer survivorship, further evidence‐based strategies and equitable access to available resources are needed to mitigate disparities for communities of color and optimize care for people with a history of cancer. CA Cancer J Clin. 2022;72:409‐436.